The Cryptococcus gattii species complex: Unique pathogenic yeasts with understudied virulence mechanisms. - Lamin Saidykhan; Chinaemerem U Onyishi; Robin C May (Public Library of Science (PLoS), 2022)
Members of Cryptococcus gattii/neoformans species complex are the etiological agents of the potentially fatal human fungal infection cryptococcosis. C. gattii and its sister species cause disease in both immunocompetent and immunocompromised hosts, while the closely related species C. neoformans and C. deneoformans predominantly infect immunocompromised hosts. To date, most studies have focused on similarities in pathogenesis between these two groups, but over recent years, important differences have become apparent. In this review paper, we highlight some of the major phenotypic differences between the C. gattii and neoformans species complexes and justify the need to study the virulence and pathogenicity of the C. gattii species complex as a distinct cryptococcal group.